IMPLEMENTASI PROGRAM P2WKSS DI KABUPATEN SUMEDANG - Suci Rahmania Arifien; Akadun; Anne Friday Safaria (LPPM UNSAP & FISIP UNSAP, 2023)
This research aims to obtain an overview of the implementation of the P2WKSS program in Sumedang Regency. The research method used is a qualitative method using purposive sampling. This research was analyzed using qualitative descriptive research with research informants, Sumedang Regency DPPKBP3A employees. The research was carried out using the Miles and Huberman model with stages including data reduction, data presentation and drawing conclusions. The research results show that it has been implemented quite well in accordance with the dimensions and objectives of the P2WKSS integrated program implementation regulations. Apart from that, other aspects also support P2WKSS activities in Sumedang Regency, such as funding sources, adequate human resources and implementation times that have been arranged in such a way that P2WKSS in Sumedang Regency can be implemented according to the activity schedule with the working group members involved in accordance with their respective main tasks and functions. -each. This cannot be separated from the implementers' openness in accepting and responding well to the existence of the integrated P2WKSS program in Sumedang Regency.